2012
DOI: 10.1161/circresaha.111.259630
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Islet-1–Positive Cells in the Healthy and Infarcted Adult Murine Heart

Abstract: Rationale The transcription factor Islet-1 is a marker of cardiovascular progenitors during embryogenesis. The isolation of Islet-1-positive (Islet-1+) cells from early postnatal hearts suggested that Islet-1 also marks cardiac progenitors in adult life. Objective We investigated the distribution and identity of Islet-1+ cells in adult murine heart and evaluated whether their number or distribution change with age or after myocardial infarction. Methods and Results Distribution of Islet-1+ cells in adult h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 32 publications
5
59
1
2
Order By: Relevance
“…However, regardless of the species -mouse, rat or human -ISL1 + cells are rare in the adult, and in the mouse they are largely confined to the sinoatrial node (Fig. 4) (Weinberger et al, 2012).…”
Section: Isl1 + Progenitor Cells Developmental Origins and Location Imentioning
confidence: 99%
See 1 more Smart Citation
“…However, regardless of the species -mouse, rat or human -ISL1 + cells are rare in the adult, and in the mouse they are largely confined to the sinoatrial node (Fig. 4) (Weinberger et al, 2012).…”
Section: Isl1 + Progenitor Cells Developmental Origins and Location Imentioning
confidence: 99%
“…Cells were marked by β-galactosidase staining (blue) from an Isl1-nuclear lacZ knock-in allele. Reproduced with permission (Weinberger et al, 2012). (B) The epicardium (shown in red, along with the coronary vessels within the myocardium) gives rise to perivascular cells and stromal fibroblasts in development, and in the adult this potential is retained, which is activated after injury.…”
Section: Endogenous Adult Cardiac Stem Cellsmentioning
confidence: 99%
“…These Isl-1 þ cells were isolated from very young animals, do not express c-kit but harbor cardiomyogenic potential both in vitro and in vivo. After 4 weeks of age, the Isl-1 þ cardiac cells lost the capacity for differentiation (Weinberger et al, 2012). Thus, Isl-1 þ cells are a population of cells with cardiac progenitor potential, but only in young hearts.…”
Section: Isl-1 1 Cscsmentioning
confidence: 99%
“…Mouse and human c-kit þ , CD31 þ , CD34 þ c-kit, CXCR4 Messina et al, 2004;Davis et al, 2009;Smith et al, 2007;Tang et al, 2009 Isl Laugwitz et al, 2005;Weinberger et al, 2012 CSCs, cardiac stem cells; CSP, cardiac side population.…”
Section: Cardiospheresmentioning
confidence: 99%
“…For instance, the IGF-1/IGF-1 receptor (IGF-1R) system preserves the pool of endogenous CSCs through enhancing telomerase activity and delaying senescence by activating the PI3K-Akt pathway, indicating that IGF-1 may protect CSCs against adverse aging effects [122]. It has been shown that the IGF-1/ IGF-1R axis exists in cardiac stem cells in very old animals, but the IGF-1 synthesis and the IGF-1R expression are found to decrease in aging human CSCs [122,125,126]. In this regard, preconditioning of cultured resident CSCs in old age by over-expressing telomerase or up-regulation of favourable growth factor signalling may improve the regenerative capabilities of survival, growth and differentiation in vivo following transplantation [104,124,127].…”
Section: Effect Of Age On Isolation and Function Of Cardiac Stem Cellsmentioning
confidence: 99%